Nurses’s Experience in Providing Spiritual Care - Nunung Rachmawati; Tenang Aristina (UIMA Press, 2022)
Background: Spiritual care is considered by nurses not as part of their duties and responsibilities, so that the spiritual needs of many patients are neglected. Spiritual care is a necessity that is often overlooked in daily nursing practice and is less a priority than physical needs because spiritual needs are often abstract, complex, and more difficult to measure. Objectives: This study aims to determine the description of the nursing experience of the “YKY” Nursing Academy alumni in providing spiritual care. Methods: This study uses a qualitative method with a phenomenological approach. The subjects in this study were the alumni nurses of the Nursing Academy